Analisis Perbandingan Sistem Hukum Islam Dan Sistem Hukum Positif - Ira Sandika; Denni Iwan Permata Saragih; Sri Hadiningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
Islamic law is one aspect of Islamic teachings which occupies a very crucial position in the view of Muslims, because it is the most concrete manifestation of Islamic law as a religion. Islamic law has a significant influence on Indonesian positive law, especially in several areas of law. Meanwhile, positive law is law in the form of laws that regulate relations between humans and humans, or with legal entities. Islamic law is generally defined as rules which are the result of understanding and deducing from the provisions revealed by Allah SWT to the Prophet Muhammad SAW. Therefore, the main sources of Islamic law are the Koran and Hadith. source of pure positive law from society. This is because the adoption or discovery of positive law uses an inductive method. Namely by observing the actions and attitudes of community members. From the results of these various observations, general regulations are then made that are binding on the entire community. In this article the author tries to explain further the analysis of the concepts and sources of these two laws, and their comparative analysis.